Advancing Sustainable Development in Jordan: A Business and Economic Analysis of Electric Vehicle Adoption in the Transportation Sector - Ghazi A. Samawi; Omar M. Bwaliez; Mohannad Jreissat; Abdallah Kandas (World Electric Vehicle Journal)
This study explores electric vehicle (EV) adoption in Jordan, focusing on key transitional factors. It examines government policies, market dynamics, technological advancements, and infrastructure development through semi-structured interviews with key stakeholders, including government officials, industry experts, and consumers. The study provides insights into the economic prospects, infrastructure requirements, and regulatory measures necessary for widespread EV adoption. Government incentives, such as tax exemptions and reduced registration fees, are crucial, but challenges like insufficient charging infrastructure, high initial costs, and limited public awareness persist. Collaborative efforts between the public and private sectors are essential to develop resilient infrastructure, enhance consumer education, and foster technological innovation. The findings underscore the importance of government incentives and coordinated efforts to develop charging infrastructure and raise public awareness. Future research should focus on quantitative methods to validate these findings and explore additional strategies to overcome identified barriers.